Hypereosinophilia and abdominopulmonary gnathostomiasis - Intapan P.M. (2014)
A 16-year-old Thai male presented with sudden onset severe epigastric and right upper quadrant pain, fever (39°C), chills and malaise. He gave no history of underlying disease, migratory swelling or urticarial skin rash. He had a history of frequently eating raw pork. Physical examination revealed a soft abdomen with markedly tender hepatomegaly. His blood count showed extreme leukocytosis with hypereosinophilia. After admission he developed a non-productive cough with left sided chest pain, a chest x-ray showed a left pleural effusion. Serological findings were positive for Gnathostoma larval antigen but not Fasciola antigen. The patient recovered completely after albendazole treatment. His clinical presentation is compatible with abdominopulmonary hypereosinophilic syndrome or visceral larva gnathostomiasis. The presented case is interesting not only for physicians who work in endemic areas of gnathostomiasis but also for clinicians who work in travel medicine clinics in developed countries, to consider abdominopulmonary gnathostomiasis when patients present with the signs and symptoms of visceral larva migrans.